2014
DOI: 10.1007/s10900-014-9926-7
|View full text |Cite
|
Sign up to set email alerts
|

HIV/STI Prevalence Study Among Military Conscripts in Estonia

Abstract: Risk taking behavior and sexually transmitted infections (STIs) research outcomes vary among militaries. A common theme indicates STI prevalence and risk taking among military personnel is higher than the general population. Alcohol and drug misuse is well documented. From these behaviors, high-risk sexual encounters increase. Exploring STI prevalence, knowledge, and risk behaviors among conscripted military forces, we recruited 584 conscripts from a defense force in Eastern Europe. The observed STI prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…We found a prevalence rate of CTI of 15.4% among the members of the SAF. This CTI prevalence is higher than previously reported in the most of other studies conducted within the military population, noting the prevalence ranging from 2.5%-9.5% 13,15,19,20 . Our results were similar to a large survey among female military recruits conducted in the United States of America in 1997.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…We found a prevalence rate of CTI of 15.4% among the members of the SAF. This CTI prevalence is higher than previously reported in the most of other studies conducted within the military population, noting the prevalence ranging from 2.5%-9.5% 13,15,19,20 . Our results were similar to a large survey among female military recruits conducted in the United States of America in 1997.…”
Section: Discussioncontrasting
confidence: 66%
“…Studies conducted in the Armed Forces of Poland 12 , Estonia 13 , Brazil 14 , Israel 15 , Slovenia 16 and the United States of America 17 , shown that CTI is common within military population. High rates of CTI among military population generate significant healthcare costs in the armies 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The US Navy and Marine Corps established a Sexual Health and Responsibility Program (SHARP) to coordinate activity in the field of STI prevention programs [46]. In line with the known preventive effects of early diagnosis and treatment [47][48][49], military entry screenings for STIs have been recommended as a strategy of reducing STIs within the military community [50]. Data evaluating the preventive effects of prevention programs addressing STIs in the military setting are, however, still missing.…”
Section: Discussionmentioning
confidence: 99%
“…KABP questionnaires are commonly used in research to identify information related to sexual behaviours and stigmas associated with STIs (16,17). The KABP questionnaire used in this project was a modified version of the assessment administered to conscripts in 2012 (18). The modified version required approximately 20 minutes to complete and included 34 questions on sexual behaviours, drug use, testing for STIs, and knowledge.…”
Section: Methodsmentioning
confidence: 99%